Both Val158Met Polymorphism of Catechol-O-Methyltransferase Gene and Menstrual Cycle Affect Prepulse Inhibition but Not Attentional Modulation of Prepulse Inhibition in Younger-Adult Females. (15th April 2019) - Wu, Chao; Ding, Yu; Chen, Biqing; Gao, Yayue; Wang, Qian; Wu, Zhemeng; Lu, Lingxi; Luo, Lu; Zhang, Changxin; Bao, Xiaohan; Yang, Pengcheng; Fan, Langchen; et al.
Abstract: Prepulse inhibition (PPI) can be modulated by both the Val158Met (rs4680) polymorphism of the Catechol-O-Methyltransferase ( COMT ) gene and the menstrual-cycle-related hormone fluctuations, each of which affects the subcortical/cortical dopamine metabolism. PPI can also be modulated by attention. The attentional modulation of PPI (AMPPI) is sensitive to psychoses. Whether the Val158Met polymorphism affects the AMPPI in female adults at different menstrual-cycle phases is unknown. This study examined whether AMPPI and/or PPI are affected by the Val158Met polymorphism in 177 younger-adult females whose menstrual cycles were mutually different across the menstruation, proliferative, or secretory phases. The AMPPI was evaluated by comparing PPI under the condition of the auditory precedence-effect-induced perceptual spatial separation between the prepulse stimulus and a masking noise (PPIPSS ) against that under the condition of the precedence-effect-induced perceptual spatial co-location (PPIPSC ). The results showed that both the menstrual cycle and the COMT Val158Met polymorphism affected both PPIPSC and PPIPSS, but not the AMPPI (difference between PPIPSS and PPIPSC ). Moreover, throughout the menstrual cycle, both PPIPSC and PPIPSS decreased monotonously in Val/Val-carrier participants. However, the decreasing pattern was not overserved in either Met/Met-carrier or Met/Val-carrier participants. Thus, in healthy younger-adult females, PPIPSC and PPIPSS, but not the AMPPI, is vulnerable to changes of ovarian hormones, and the COMT Val158Met polymorphism also has a modulating effect on this menstrual-cycle-dependent PPI variation. In contrast, the AMPPI seems to be more steadily trait-based, less vulnerable to ovarian hormone fluctuations, and may be useful in assisting the diagnosis of schizophrenia in female adults. Highlights: In healthy younger-adult females, PPI is vulnerable to ovarian hormones changes. Their PPI is modulated by both Val158Met polymorphism and menstrual cycle. Their attentional modulation of PPI is not affected by menstrual cycle. Their attentional modulation of PPI is not affected by Val158Met polymorphism. Attentional modulation of PPI is more steadily trait-based.